2017
DOI: 10.2147/copd.s134998
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between fractional exhaled nitric oxide and sputum eosinophilia in exacerbations of COPD

Abstract: IntroductionMeasurements of eosinophils in induced sputum and fractional exhaled nitric oxide (FeNO) are noninvasive biomarkers for assessing airway inflammation phenotypes in chronic obstructive pulmonary disease (COPD). Nevertheless, the clinical application of the correlation between FeNO levels and sputum eosinophilia is controversial. The study aimed to investigate the correlation and predictive relationship between FeNO levels and sputum eosinophils in patients with COPD exacerbation. It also examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 11 publications
0
22
3
2
Order By: Relevance
“…A cutoff of 2% peripheral blood eosinophils had a sensitivity of 90% and specificity of 60% for identifying a sputum eosinophilia of greater than 3% at exacerbation [19]. Our previous research had revealed that peripheral percentage blood eosinophil (> 0.65%) [11] can be a very good biomarker of sputum eosinophilic airway inflammation in COPD exacerbations (AUC 0.729, sensitivity =74.2%, specificity =61.4%), the optimal cut offs (0.65%) are similar to the result (> 0.55%) in this study. Blood eosinophil ratios, such as ENR, ELR and EMR, also seemingly predicted sputum eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cutoff of 2% peripheral blood eosinophils had a sensitivity of 90% and specificity of 60% for identifying a sputum eosinophilia of greater than 3% at exacerbation [19]. Our previous research had revealed that peripheral percentage blood eosinophil (> 0.65%) [11] can be a very good biomarker of sputum eosinophilic airway inflammation in COPD exacerbations (AUC 0.729, sensitivity =74.2%, specificity =61.4%), the optimal cut offs (0.65%) are similar to the result (> 0.55%) in this study. Blood eosinophil ratios, such as ENR, ELR and EMR, also seemingly predicted sputum eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood cells may be a potential alternative to quantify sputum inflammatory cells to detect airway inflammatory phenotypes. Recent reports have demonstrated the association between sputum and blood eosinophils in COPD [10,11]. And the 2018 Global Initiative for Chronic Obstruction Lung Disease (GOLD) published an evidence-based clinical research guideline that blood eosinophils (> 2%) can predict the risk of exacerbations [1].…”
Section: Introductionmentioning
confidence: 99%
“…e FeNO test has been increasingly used because it can easily and noninvasively measure NO. FeNO is also known to be associated with various interleukins, cytokines, and sputum eosinophilia [27,28]. erefore, FeNO is considered a test reflecting airway inflammation and airway hyperresponsiveness [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Gao levels were predictive of sputum eosinophilia. 58 Validation of assays, however, as well as interpretation of clinical impact require solution before implementation in practice.…”
Section: Exhaled Breath Analysismentioning
confidence: 99%